2021
DOI: 10.3390/s21124142
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tentacle Gripper for Pipe Crawling to Inspect Industrial Facilities Using UAVs

Abstract: This paper presents a crawling mechanism using a soft-tentacle gripper integrated into an unmanned aerial vehicle for pipe inspection in industrial environments. The objective was to allow the aerial robot to perch and crawl along the pipe, minimizing the energy consumption, and allowing to perform contact inspection. This paper introduces the design of the soft limbs of the gripper and also the internal mechanism that allows movement along pipes. Several tests have been carried out to ensure the grasping capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Work from this challenge has been mention in the following section. [Fiaz et al, 2017, Fiaz et al, 2018, Gawel et al, 2017, Sutera et al, 2020, Bahnemann et al, 2017, Spurný et al, 2019 Medium Low High Vacuum [Kessens et al, 2019, Liu et al, 2020, Kessens et al, 2016, Tsukagoshi et al, 2015 Medium Medium High Tendon [Hingston et al, 2020, Gomez-Tamm et al, 2020, Fishman et al, 2021, Garcia Rubiales et al, 2021, McLaren et al, 2019, Pounds et al, 2011, Backus et al, 2014, Kruse and Bradley, 2018, Popek et al, 2018 Medium Medium Medium…”
Section: Aerial Graspingmentioning
confidence: 99%
See 3 more Smart Citations
“…Work from this challenge has been mention in the following section. [Fiaz et al, 2017, Fiaz et al, 2018, Gawel et al, 2017, Sutera et al, 2020, Bahnemann et al, 2017, Spurný et al, 2019 Medium Low High Vacuum [Kessens et al, 2019, Liu et al, 2020, Kessens et al, 2016, Tsukagoshi et al, 2015 Medium Medium High Tendon [Hingston et al, 2020, Gomez-Tamm et al, 2020, Fishman et al, 2021, Garcia Rubiales et al, 2021, McLaren et al, 2019, Pounds et al, 2011, Backus et al, 2014, Kruse and Bradley, 2018, Popek et al, 2018 Medium Medium Medium…”
Section: Aerial Graspingmentioning
confidence: 99%
“…Rigid Joints [Hingston et al, 2020, Gomez-Tamm et al, 2020, Pounds et al, 2011, Backus et al, 2014, Kruse and Bradley, 2018, Popek et al, 2018] Soft Joints [Fishman et al, 2021, Garcia Rubiales et al, 2021, McLaren et al, 2019…”
Section: Research Problem Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid prototyping technologies, such as additive manufacturing (AM), allow the fabrication of assembly parts of such systems [19][20][21]. Numerous studies have shown the possibilities of rapid prototyping technologies and their application [22,23].…”
Section: Introductionmentioning
confidence: 99%